2011
DOI: 10.1007/s10286-011-0141-7
|View full text |Cite
|
Sign up to set email alerts
|

Syncopal migraine

Abstract: Syncope may have a migrainous basis more commonly than previously suspected, and we suggested criteria to identify these patients. Syncopal migraine appears epidemiologically more closely related to migraine than to reflex syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Also among adult females the migraine was associated with syncope [46] and carried a higher risk for ortostatic intolerance [47]. Curfman et al [48] reported that nearly one-third of their recurrent syncope subjects met the criteria for syncopal migraine. Clinically they had similar clinical complaints as other migranours, and the anti-migraine treatment reduced syncope in half of the syncope migraine subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Also among adult females the migraine was associated with syncope [46] and carried a higher risk for ortostatic intolerance [47]. Curfman et al [48] reported that nearly one-third of their recurrent syncope subjects met the criteria for syncopal migraine. Clinically they had similar clinical complaints as other migranours, and the anti-migraine treatment reduced syncope in half of the syncope migraine subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Because migraine can be a lifelong condition, patient education on preventive strategies that minimize the impact on the individual’s life and reduces the potential occurrence of a migraine related complication is essential. There are many diseases that have been identified as comorbidities of migraine, such as restless legs syndrome (RLS) [2], hypertension [3], syncope [4], depression [5] and increased risk of vascular incidents [6]. These conditions eventually contribute to the overall morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…18 Interestingly, the link between migraine headaches and syncope is also well established, bolstering Menière’s clinical diagnosis of migraine headaches in his patients. 19,20 …”
Section: Discussionmentioning
confidence: 99%